Conditionally accepted : Christians' perspectives on sexuality and gay and lesbian civil rights - Rogers, Baker A. (Rutgers University Press, 2019)
This book explores Mississippi Christians' beliefs about homosexuality and gay and lesbian civil rights and whether having a gay or lesbian friend or family member influences those beliefs. Beliefs about homosexuality and gay and lesbian rights vary widely based on religious affiliation. Despite having gay or lesbian friends or family members, evangelical Protestants believe homosexuality is sinful and oppose gay and lesbian rights. Mainline Protestants are largely supportive of gay and lesbian rights and become more supportive after getting to know gay and lesbian people. Catholics describe a greater degree of uncertainty and a conditional acceptance of gay and lesbian rights; clear differences between conservative and liberal Catholics are evident. Overall, conservative Christians, both evangelical Protestants and conservative Catholics, hold a religious identity that overshadows their relationships with gay and lesbian friends or family. This book argues that conservative religion acts as a deterrent to the positive benefits of relationships with gay and lesbian people.